KAJIAN PEMANFAATAN LIMBAH NILAM UNTUK PUPUK CAIR ORGANIK - Soraya Santi, Sintha (Jurnal Teknik Kimia, 2008)
Waste of the distillation of pogestemon cablin still havet high nutrient content and potentialas a good raw material of organic fertilizer . Rapid composting technology and efficient organicfertilizer will produce high quality compost. This study aim to determine the best conditions in termsof fermentation time 6,10,14,18,22 day and volume of bacteria (EM4): 2,4,8,10% EM4/solution wereadded to the N, P, K most in the process of making liquid fertilizer to use waste leaves the distillationof pogestemon cablin of N, P and K respectively 10.6% weight, 1.19% and 3.08% heavy weight andthe volume EM4 8% and the fermentation time of 14 days.Key words : pogestemon cablin, fermentation, ,liquid organic fertilizer, nitrogen,kalium, phospor